2020
DOI: 10.1097/jom.0000000000001873
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness Evaluation of Career Urban and Wildland Firefighters

Abstract: Objective: Examine the physical fitness of career firefighters and compare their results to normative data and suggested standards for their profession. Methods: Eighty firefighters completed a body composition analysis, maximal aerobic capacity (VO2max) test, and fitness testing battery, with results compared with normative value tables. Maximal aerobic capacity was correlated to fitness measures and differences between VO2max quartiles were examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
1
15
2
Order By: Relevance
“…Hauschild et al [ 25 ], in a systematic review of correlations between fitness tests and discrete occupational tasks amongst 27 different studies within the tactical athlete population (13 military population; 10 FF, law enforcement, or peace officer; and 4 healthy civilian populations), found that HG dynamometry test was strongly correlated ( r ≥ 0.5) with one-quarter (i.e., lift and lower [single] task with r = 0.67, p < 0.05; lift and lower [repeated] task with r = 0.59, p < 0.05; stretcher carry task with r = 0.61, p < 0.05) of the 12 occupational tasks categories by which the authors examined relationships with it. However, the mean maximal HG strength in studies of FFs’ work capacity range from 47 to 61 kg for men, showing that the maximal HG strength in our current research study (33.1 kg ± 7.8 kg) does not fall within norms of previous research studies [ 32 , 40 , 52 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Such discrepancy may be explained by the fact that, in our protocol, FFs wore their full occupational firefighting gear including their tactical gloves, while the prior research studies either did not use PPE, used parts of it, or did not use a control trial.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Hauschild et al [ 25 ], in a systematic review of correlations between fitness tests and discrete occupational tasks amongst 27 different studies within the tactical athlete population (13 military population; 10 FF, law enforcement, or peace officer; and 4 healthy civilian populations), found that HG dynamometry test was strongly correlated ( r ≥ 0.5) with one-quarter (i.e., lift and lower [single] task with r = 0.67, p < 0.05; lift and lower [repeated] task with r = 0.59, p < 0.05; stretcher carry task with r = 0.61, p < 0.05) of the 12 occupational tasks categories by which the authors examined relationships with it. However, the mean maximal HG strength in studies of FFs’ work capacity range from 47 to 61 kg for men, showing that the maximal HG strength in our current research study (33.1 kg ± 7.8 kg) does not fall within norms of previous research studies [ 32 , 40 , 52 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Such discrepancy may be explained by the fact that, in our protocol, FFs wore their full occupational firefighting gear including their tactical gloves, while the prior research studies either did not use PPE, used parts of it, or did not use a control trial.…”
Section: Discussioncontrasting
confidence: 64%
“…Stair climbing protocols have been used amongst researchers to assess anaerobic performance in various tactical athlete populations, including FFs [ 24 , 32 , 61 , 71 , 72 , 73 ]. Clarke [ 24 ] introduced a tower climb test (TCT) to assess anaerobic performance in urban FFs and found that staircase protocols provided an occupationally specific mean by which to measure anaerobic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies have reported relationships between muscular strength, power, and anaerobic endurance with a firefighter’s ability to perform essential occupational tasks such as a victim drag, equipment hoist, ladder carry, stair climbing, and hose deployment [ 245–247 ]. Thus, high levels of both aerobic and muscular fitness have been recommended for adequate occupational performance for both structural and wildland firefighters [ 248 ].…”
Section: Part 2 – First Respondersmentioning
confidence: 99%
“…28 Body composition, cardiorespiratory fitness, muscular strength and endurance have been reported to decrease throughout their careers and as they age, particularly those that are physically inactive. [29][30][31][32][33][34] Maintenance of good overall levels of health-related physical fitness is crucial for career longevity and overall well-being in firefighters. 2 35 36 In addition, firefighters have been reported to have the highest incidence of musculoskeletal injuries among all emergency services personnel.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Health-related physical fitness includes body composition, cardiorespiratory fitness, muscular strength, muscular endurance and flexibility 28. Body composition, cardiorespiratory fitness, muscular strength and endurance have been reported to decrease throughout their careers and as they age, particularly those that are physically inactive 29–34. Maintenance of good overall levels of health-related physical fitness is crucial for career longevity and overall well-being in firefighters 2 35 36…”
Section: Introductionmentioning
confidence: 99%